Effects of traffic patterns on vehicle pollutant emission factors in road tunnels - Yan, Guanfeng; Wang, Mingnian; Yan, Tao; Qin, Pengcheng (Tunnelling and underground space technology, 2022)
[Display omitted] •Air velocity of one-way two-bore tunnels is higher than that with only one bore.•A new formula is presented to predict air velocity for two-way tunnels.•Pollutant emission factors increase in two-way one-bore tunnels.•Two-way one-bore tunnels suit low-level roads with a small traffic volume. Vehicles are travelling in both directions inside one bore for two-way one-bore ones where traffic force in one direction can be partially offset due to the existence of air movement induced by the vehicles travelling in the other direction. The pollutant emission factors of two-way one-bore tunnels may increase since the traffic force is beneficial for pollutant discharge. In this study, one bore of two road tunnels was blocked for maintenance for a period, and the traffic pattern of the two tunnels turned from the one-way two-bore into the two-way one-bore. A series of field experiments have been conducted under these two traffic patterns. The results show that the air velocity is lower for two-way one-bore tunnels because the traffic force is offset in two directions. A formula is proposed to predict the air velocity for two-way one-bore tunnels and validated by field measurements. Compared with one-way two-bore tunnels, pollutant concentrations and emission factors are higher for two-way one-bore ones and influenced by the ratio of traffic volume in two directions. What’s more, the pollutant emitted by the vehicles in the other direction also contributes to the increase in the emission factors for two-way one-bore tunnels. Consequently, one-way two-bore tunnels have an advantage in pollutant discharge, and two-way one-bore tunnels are recommended only for regions with a small traffic volume to reduce the construction and operation costs.